Elaboración de un plan de mantenimiento preventivo para la cortadora de plasma CNC Combirex 4000 de la empresa metalmecánica Idemec S.A. (2020)
For the development of the project, it started by collecting the necessary information about the company Idemec S.A. and its production process, as well as the equipment involved, the function performed and the products that they offer. Similarly, it collected everything related to maintenance performed on equipment, what has been made, who performs, how and at what intervals of time. With this information, continued to analyze the importance of each and every one of the consequences that would be generated if some machines comes to stop or present a problem, by which was made an analysis of criticality resulting in major machine is the CNC Combirex 4000 plasma cutter.